Population Dynamics of Microarthropods (Oribatida and Collembola) in Rainfed Paddy Field Ecosystem in Pati, Central Java - Rahayu Widyastuti (Jurnal Ilmu Tanah dan Lingkungan, 2005)
A study on population dynamics of microarthropods (oribatids and collembolans) in rainfed paddy field ecosystem inPati, Central Java was undertaken with the aim to evaluate which group of soil microarthropods that dominated in each phase of rain fed paddy field. The soil fauna was collected using a soil corer of20 cm diameter to a depth of 0-15 cm, every 30 days.In the fallow, soil fauna was sampled from 4 randomized points per plot, meanwhile in the rice field phases (dry seeded rice and transplanted rice), it was sampled from 4 randomized points in the fields and in the bunds, respectively. per plot. Soil microarthropods in each season were then extracted in a Berlese funnel extractor.During the fallow phase, the dominant soil microarthropods were Oribatida of the Acari (1200 individual m,l) andsome groups of Collembola, namely Hypogastruridae (/200 individual m:2), Entomobryidae (500 individual m,l) andIsotomidae (620 individual m,2), meanwhile Sminthuridae of Collembola did not appear in this phase. In the rice phase,however, Sminthuridae of the Collembola occurred in high numbers, i.e., 860 individual m,2 (field) and 6/0 individual m,l(bund).Regarding the population dynamics of soil microarthropods in rainfed paddy field, we can assumed that oribatids and some groups of collembolans (Hypogastruridae, Entomobryidae and Isotomidae) play an important role in improving the nutrient availability during the fallow phase. meanwhile the Sminthuridae of collembolan seemed to play such role in the rice field phase. more than the other soil microarthropods.